Degradable Superhydrophilic Iron‐Pillared Bentonite Doped with Polybutylene Adipate/Terephthalate Open‐Cell Foam: Its Application in Dye Degradation, Removal of Heavy Metal Ions, and Oil–Water Separation. Issue 12 (13th September 2021) - Qiu, Liyan; Phule, Ajit Dattatray; Zhong, Weipeng; Wen, Shibao; Zhang, Zhenxiu
Abstract: Development of industrialization has brought convenience to people's lives; however, it has also brought serious harm to the environment, where, water pollution is the most obvious. Here, a polybutylene adipate terephthalate (PBAT) open‐cell foam doped with iron‐pillared bentonite (IPB) is prepared by using sugar as a pore‐forming agent and solution phase separation, and then combined with a solution dipping method to coat the foam surface with a polyacrylamide/SiO2, which makes the PBAT foam superhydrophilic. The static adsorption effect of superhydrophilic IPB‐doped PBAT open‐cell foam on methylene blue (MB) and Cu 2+ is studied. The adsorption isotherm fitting shows that the adsorption conforms to the Langmuir model and it has biased toward monolayer adsorption. The adsorption kinetics fitting confirms that the adsorption process is in line with the pseudo‐second‐order adsorption model, which is dominated by chemical adsorption. The modified PBAT open‐cell foam has an adsorption effect on Cu 2+ ; however, it has weak cyclic adsorption capacity. It shows a good cyclic adsorption ability for the cationic dye MB and it has >95% photodegradation efficiency of the MB after five time's cyclic adsorption. The superhydrophilicity makes the foam to have better applications in oil–water separation. Abstract : The modified polybutylene adipate terephthalate (PBAT) foam shows superhydrophilicity which can be used for oil–water separation. The modified PBAT foam can remove cationic dye methylene blue (MB) and Cu 2+ through the cation exchange capacity and surface electronegativity of the embedded iron‐pillared bentonite, which forms a Fenton‐like reaction system with hydrogen peroxide under light conditions, causing MB to undergo photodegradation.